RATIO LEGIS OF THE IMPLEMENTATION OF THE STRENGTH OF THE DECISION OF THE CONSUMER DISPUTE RESOLUTION BODY IN RESOLVING DISPUTES - Dahris Siregar; Karolina Sitepu; Elyani Elyani (LPPM Universitas Ekasakti Padang, 2023)
In Indonesia, there are 2 (two) ways to resolve disputes between business actors and consumers, namely by litigation and non-litigation. Dispute resolution process dispute resolution process through court channels or what is also called litigation will take a relatively long time. relatively long time. Meanwhile, on the contrary, settlement through non-litigation litigation, namely through one of the quasi-judicial institutions, namely the Consumer Dispute Settlement Body, which is mandated by Law Number 8 Year 1999 on Consumer Protection. 1999 on Consumer Protection. The research results show that settlement of consumer disputes through the Consumer Dispute Settlement Body (BPSK) can be considered ineffective. This is evidenced by the fact that there are still many parties who do not agree with BPSK's decision. This is also supported by several obstacles contained in it.